ANALISIS PROFITABILITAS, SOLVABILITAS DAN LIKUIDITAS UNTUK MENILAI KINERJA KEUANGAN PT SAMCRO HYOSUNG ADILESTARI Tbk TAHUN 2023-2024 - Pardede Mazmur; Daniel Niscon Simanjuntak (Jurnal Penelitian Samudra, 2025)
This study evaluates the financial performance of PT Samcro Hyosung Adilestari Tbk for the fiscal year 2023 and the nine-month period ending September 30, 2024. The analysis employs three fundamental financial ratios: liquidity (Current Ratio and Quick Ratio), solvency (Debt to Asset Ratio - DAR and Debt to Equity Ratio - DER), and profitability (Net Profit Margin - NPM). The company's performance is assessed against specific industry standards: a Current Ratio ideal of 2.0x, a Quick Ratio ideal of 1.5x, a DAR ideal of 35%, a DER ideal of 90%, and an NPM ideal of 20%. In conclusion, PT Samcro Hyosung Adilestari Tbk transitioned from a financially vulnerable position in 2023 to one of exceptional strength in liquidity, solvency, and profitability by 2024, largely due to successful strategic financial restructuring. This enhanced financial standing positions the company favorably for future growth and stability.